The inflation expectations of firms: What do they look like, are they accurate, and do they matter? - Michael F. Bryan; Brent H. Meyer; Nicholas B. Parker (Federal Reserve Bank of Atlanta, 2014)
The purpose of this paper is to answer the three questions in the title. Using a large monthly survey of businesses, we investigate the inflation expectations and uncertainties of firms. We document that, in the aggregate, firm inflation expectations are very similar to the predictions of professional forecasters for national inflation statistics, despite a somewhat greater heterogeneity of expectations that we attribute to the idiosyncratic cost structure firms face. We also show that firm inflation expectations bear little in common with the "prices in general" expectations reported by households. Next we show that, during our three-year sample, firm inflation expectations appear to be unbiased predictors of their year-ahead observed (perceived) inflation. We demonstrate that firms know what they don't know - that the accuracy of firm inflation expectations are significantly and positively related to their uncertainty about future inflation. And lastly, we demonstrate, by way of a cross-sectional Phillips curve, that firm inflation expectations are a useful addition to a policymaker's information set. We show that firms' inflation perceptions depend (importantly) on their expectations for inflation and their perception of firm-level slack.
Keywords: E31; C81; C90; E60; E37; 330; inflation; survey inflation expectations; price formation